Urban cultural intermediaries: Reflections on pedagogy and creativity in the urban economy. (May 2019) - Vickery, Jonathan
This article is a critical reflection on a creative practice course module that runs each year in the city of Coventry. The module aims to develop student skills appropriate to the creative and cultural industries, while maintaining an emphatic radical dimension in raising the students' social consciousness on the urban context of their skills development. Between 2016 and 2018 the module attracted funding in order to enhance its strategic approach to creative pedagogy through research and a revised module structure. This article charters this development and articulates the broader critical implications of using 'creativity' in higher education. Students were cast as 'cultural intermediaries' in knowledge production – exhibiting and debating in public the outcomes of urban research. This article is not a detailed evaluation of the project, which given its complexity is not possible in one article, but identifies the limits and fault lines of an intended development of a critical pedagogy for students in the urban cultural economy.